ANALYSIS OF RELATIONSHIP OF MARKETING MIX WITH THE VALUE OF THE SALE OF FRUITS AT FRUIT MARKET TRADERS IN KENDARI CITY - Diana Pratiwi Sa’Pangan; Helviani Helviani (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
This study aimed to analyze the marketing mix (product, price, place and promotion) of fruits at the level of traders in fruit market Kendari, and to analyze the relationship between the marketing mix (product, price, place and promotion) with sales of fruit- fruits at the level of traders in fruit market Kendari. Determining the location of this research is done purposively (intentionally) on the basis that at the fruit market of Kendari in question is central sale of various kinds of fruits. The variables observed were: 1) a variable reinforcement, namely the identity of respondents include: the merchant name, age, level of formal education, and business experience, 2) main variables include: the marketing mix (product, price, place, promotion) and value sale. Analysis of the data used is descriptive qualitative analysis to analyze the marketing mix (product, price, place and promotion) of fruits at the level of traders in fruit market Kendari, and correlation analysis Spearman to analyze the relationship between the marketing mix (product, price, place, and promotion) with a sales value of fruit. The results showed that the implementation of any marketing mix in the fruit market of Kendari which aspects of the product and the price aspect is quite good, very nice aspect of the place, and the promotional aspect has not done well. There is a relationship between each of the marketing mix with a sales value of fruit, each worth: a) products with a sales value = 0.493, which means the level of relationship is or is strong enough, b) the price of the sales value = 0.436, which means the level of relationship is or reasonably strong, c) a place with a sales value = 0.620* which means the level of strong relations, d) sale with a sales value = 0.295 which means the rate of low or weak ties.